Empirical studies in trade, structural change and growth - John, Allyson Alisha (2016)
There is a general consensus regarding the positive relationship between trade and productivity growth. Openness to trade encourages an efficient allocation of the factors of production within that trade. This thesis encompasses three studies that analyse the relationships between trade policy and openness and economy-wide productivity growth and its components through different channels. In doing so, we attempt to add to the existing literature on international trade, while accounting for some observed shortcomings in the existing literature. Firstly, empirical studies examining relationships between trade, resource allocation and economy-wide productivity tend to focus only on developing economies and as such our studies comprise a mix of developed and developing nations. Furthermore, in the case of productivity growth, attention is usually biased in favour of looking at aggregate productivity, potentially missing important details at a disaggregated level. We account for this by conducting studies using disaggregated data so that we can identify any patterns or trends that may be masked by aggregate data. In addition to this, the trade-growth literature faces criticisms regarding its inability to identify an exogenous measure of trade and as such we employ the use of an exogenous instrument for trade to conduct a study on trade and productivity.